Atalay: Community Members, Not Scientists, Give Best Advice - Laura Reimer (The University of Alabama, 2022)
Review of the book: Sonya Atalay, Community-Based Archaeology: Research with, by, and for Indigenous and Local Communities. Berkeley, CA: University of California Press, 2012, 312 pages. ISBN: 9780520273368